Clinical evaluation of swallowing and dysphagia management in a patient with total mandibulectomy and primary reconstruction - P, Manju Mohan; M T, Friji; S, Dinesh Kumar; Mohapatra, Deviprasad (Journal of All India Institute of Speech and Hearing, 2013)
Dysphagia is an important postoperative problem in patients undergoing mandibulectomy. Mandibulectomy causes limitation of lip and jaw movements and subsequent slowing of oral stage of swallowing. Extensive resection of floor of mouth and bulky flap reconstructions also impair swallowing by reducing pharyngeal mobility and initiation of pharyngeal swallow. Radiotherapy (either pre- or post-op) may cause dryness of the mouth and fibrosis of the tissues which may further hinder swallowing and speech. Swallowing rehabilitation is a specialized area of speech pathology, but in the Indian scenario, practice in the realm of speech and swallowing management of head and neck cancer patients is limited. Efficient diagnosis and time bound goal directed therapy can improve the communication and swallowing problems in patients with total mandibulectomy and reconstruction. This article discusses the issues of swallowing in patients following total mandibulectomy and primary reconstruction that need to be addressed by SLP’s.